Axisymmetric waves in laminated composite incompressible materials with initial stresses under the slipping of layers - Glukhov, A.Yu. (Reports of the National Academy of Sciences of Ukraine, 2016)
The propagation of axisymmetric elastic waves in laminated composite incompressible materials with the slipping of layers is investigated within the framework of a linearized elasticity theory for bodies with initial stresses. The propagation of waves along the layers is considered. The dispersion equation for quasitransversal waves and its long-wave approximation are obtained.